Gambaran Pengetahuan, Sikap, Kepercayaan Perilaku dan Kepatuhan Mahasiswa terhadap Protokol Kesehatan Pada Masa Pandemi Covid-19 - Oktaviani Fitriyah; Nurul Haliza; Siti Nur Rofiatul Hidayah; Devi Rifqi Ayuningtyas; Indah Sulistyowati; Tanjung Anitasari Indah Kusumaningrum (Lembaga Pengembangan Kinerja Dosen, 2024)
On March 2 2020, Indonesia reported its first case of COVID-19, which has since continued to increase. The relationship with knowledge, attitudes, behavioral beliefs and compliance with COVID-19 protocols has continued. This is a descriptive quantitative research conducted on 72 active students in the Undergraduate Study Program at Muhammadiyah University of Surakarta using a sampling technique in the form of accidental sampling. The data analysis carried out was univariate analysis to describe descriptively the variables studied. The research results found that students' knowledge, attitudes, behavioral beliefs and compliance in preventing COVID-19 were quite good during the COVID-19 pandemic. There are 80% of students who have high knowledge, 79% of students have high attitudes and behavioral beliefs, and 87% of students have high compliance with health protocols. Students have the knowledge, attitude, believe that health protocols are very useful for preventing COVID-19, and comply with health protocols well. Efforts are needed to maintain good student compliance from time to time by increasing student awareness of the benefits of health protocols for themselves.